Association of leisure activity changes and reversion from mild cognitive impairment to normal cognitive function among older adults: A prospective cohort study - Xu, Xin Yi; Wang, Shan Shan; Niu, Li; Leung, Isaac Sze Him; Tian, Qing Bao (Frontiers in Public Health, 2022)
Background Older adults with mild cognitive impairment (MCI) have the possibility of reverting to normal cognitive function. Leisure activity engagement (LAE) plays a critical role in the progress of the cognitive function. A better understanding of the dynamic relationship between LAE and MCI reversion would inform the implementation of preclinical dementia interventions. This study aimed to investigate the association between change patterns of LAE and MCI reversion among older adults using the Chinese Longitudinal Healthy Longevity Survey (CLHLS) database. Study design Longitudinal population-based study. Methods Older adults with MCI at the baseline were enrolled in this study. Information about cognitive function, overall, cognitively stimulating, physically active/demanding, and socially engaged LAE was collected at baseline and follow-up. Adjusted hazard ratios (HRs) for reversion and 95% confidence intervals (CIs) were calculated by Cox hazard models with time as the underlying time metric. We also assessed potential effect modifications by creating a cross-product of the stratifying variable with LAE change patterns in the fully adjusted model. Results The restricted cubic spline showed that the association between LAE change scores and MCI reversion rate was statistically significant and nonlinear (p<0.01). Taking participants in the low–low group as a reference, participants in the low–medium, low–high, medium–medium, medium–high, high–medium, and high–high groups had increased possibilities of MCI reversion with HRs (95% CI) of 2.19 (1.57–3.06), 2.97 (2.13–4.13), 0.87 (0.64–1.19), 2.28 (1.71–3.03), 2.78 (2.10–3.69), 1.93 (1.43–2.59), and 2.74 (2.09–3.60), respectively. Further stratified models showed that the impact of LAE change patterns on MCI reversion varied in different ages (nonagenarian, octogenarian, and younger elderly) and gender. Conclusions Participants who maintained the highest LAE had the greatest possibility of MCI reversion. Meanwhile, a higher level of LAE maintenance was associated with the increased possibility of MCI reversion. These results provide a practical message to older adults about how dynamic changes in LAE are associated with improved cognitive function.